Employing Website in Japanese Learning as an Instructional Media for Pedagogical Purpose - Herniwati Herniwati; Noviyanti Aneros; Melia Dewi Judiasri (Faculty of Humanities, Universitas Jenderal Soedirman, 2019)
Industrial revolution 4.0 in the development of instructional media for Japanese language learning is one of the demands of the era that cannot be avoided anymore. Devices that cannot be released from the students' hands make it seems like it's the only source to search for information or answer in the learning process. Learning Japanese is not only through textbooks, but students are able to develop the teaching materials in the form of narratives of tourism and cultural destinations in the city of Bandung using Japanese. Those narratives about the information of destinations are packaged into a website that can be accessed anytime and anywhere, as an interactive instructional media that can increase motivation and interest about the city of Bandung in Japanese. The development of this website is not only for Japanese learners, but also useful as a source of information for Japanese people who will visit the city of Bandung. The latest information about the city of Bandung using Japanese consists of historical sites, tourist attractions, museums, and culinary. Japanese learners can access them at any time and can be used as a medium for discussion, and learners can explain it again about the city of Bandung to their friends. This innovation of learning media is a solution in the era of industrial revolution 4.0 to improve Japanese language skills both orally and in writing.